Kontribusi wisata bahari terhadap kesejahteraan masyarakat pesisir pulau Nusa Penida, Klungkung - Ni Made Santi; Yulius Hero; Hadi Susilo Arifin (Jurnal Kajian Bali (Journal of Bali Studies), 2017)
Bali’s marine resources is an important economy asset as well as food resource for local community and marine tourism. Nusa Penida Island is located in Nusa Penida District, Klungkung Region, Bali Province. It is belonging to the coral triangle area, the highest marine biodiversity in the world. Based on Decision Letter from Ministry of Marine and Fishery number 24/2014 about Nusa Penida Marine Conservation Area in Klungkung Region, Nusa Penida marine area was designated as Marine Tourism Park. Most of coastal communities in Nusa Penida are seaweed farmer. Marine tourism activity has significant impact for community’s life. Integrated development is required to be done for its sustainability. The objective of this study is to analyze marine tourism contribution for community’s prosperity in coastal area of Nusa Penida Island. Purposive sampling is chosen to collecting field data trough interview and questionnaire in 30 respondents and analyzed used BPS’s indicator (2011). As much as 90% of coastal community in Nusa Penida is categorized in moderate living condition. Marine tourism activity contributes about 36% of local income, it’s mean that marine tourism activity in Nusa Penida give positive contribution for local communities’ prosperity.